2019
DOI: 10.1021/acs.jpcc.9b09285
|View full text |Cite
|
Sign up to set email alerts
|

NMR 1D-Imaging of Water Infiltration into Porous Bitumen-Salt Matrices: The Effect of Salt Solubility

Abstract: We investigate water infiltration in porous matrices made of bitumen and salts with different solubilities. Dispersion, inside bitumen, of either SrSO4 or MgSO4 at 40% mass fraction was achieved, as a way to model materials used in the context of nuclear waste conditioning. Pulsed field gradient nuclear magnetic resonance (PFG-NMR) and environmental scanning electron microscopy (ESEM) measurements allow us to characterize the evolution of the porous structure as a consequence of water infiltration (due to a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…Dwmat$D_w^{mat}$ and Dsmat$D_s^{mat}$ calibrated on M5_NaNO3_M35_BaSO4 are 275 and 143 times larger than those in the mono‐salt NaNO 3 matrix, respectively. This significant increase of diffusion coefficients in the presence of poorly soluble salts is consistent with the existing results in the literature, 15–17 which reported that the insoluble salts finely dispersed in a bitumen matrix enhance the water progression in the material. The experimentally observed acceleration effect in the presence of BaSO 4 crystals (cf.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Dwmat$D_w^{mat}$ and Dsmat$D_s^{mat}$ calibrated on M5_NaNO3_M35_BaSO4 are 275 and 143 times larger than those in the mono‐salt NaNO 3 matrix, respectively. This significant increase of diffusion coefficients in the presence of poorly soluble salts is consistent with the existing results in the literature, 15–17 which reported that the insoluble salts finely dispersed in a bitumen matrix enhance the water progression in the material. The experimentally observed acceleration effect in the presence of BaSO 4 crystals (cf.…”
Section: Discussionsupporting
confidence: 92%
“…This observation indicates that the presence of the poorly soluble salt BaSO 4 accelerates the leaching process and the approach toward the stabilization phase. This observation is consistent with the existing nuclear magnetic resonance (NMR) results in the literature, 15,16 which suggests that insoluble salts dispersed in the bitumen matrix enhance the water progression in the material and thereby increase its water uptake rate and the resulting swelling.…”
Section: Bi-salt M5_nano3_m35_baso4 Bwpssupporting
confidence: 92%
See 3 more Smart Citations